3x(2)-23x+30=0

Simple and best practice solution for 3x(2)-23x+30=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(2)-23x+30=0 equation:


Simplifying
3x(2) + -23x + 30 = 0

Reorder the terms for easier multiplication:
3 * 2x + -23x + 30 = 0

Multiply 3 * 2
6x + -23x + 30 = 0

Reorder the terms:
30 + 6x + -23x = 0

Combine like terms: 6x + -23x = -17x
30 + -17x = 0

Solving
30 + -17x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -17x = 0 + -30

Combine like terms: 30 + -30 = 0
0 + -17x = 0 + -30
-17x = 0 + -30

Combine like terms: 0 + -30 = -30
-17x = -30

Divide each side by '-17'.
x = 1.764705882

Simplifying
x = 1.764705882

See similar equations:

| x=130(.11)+25 | | y=45(2200)+4500 | | 4x+13=79 | | 18-x=2x-3 | | 3x+37=6x-8 | | 3x^2-4=7 | | n^2-4n+1=5 | | 5(d-2)+d=13*2d | | 0.5x+70=90 | | 3x+11=-3 | | 4.3(5.6+c)= | | 5x+64=44 | | 2x+39=15 | | 4.2r+8.1s+1.09r+6.32s= | | 6x-85=-37 | | 4x+86=58 | | 2x+10=-52 | | h=-4.9t^2+1.5t+17 | | 18+27m-29+36m= | | 7=-x-10 | | 8(j+12)+4(k-19)= | | 6x+7=-35 | | 9.8c+8d-4.6c+2.9d= | | 8=53-9y | | 5+3(x+7)+10=42 | | x+x*0.35=100 | | s^2-7s+16=0 | | (x+72)(x-8)=0 | | 3x-36=-33 | | 7-4(x+8)+9=35 | | x^2+2x-10=20 | | x^2+y^2=2.25 |

Equations solver categories